Prospective study of outcome of trimalleolar ankle fractures - S., Shreekantha K.; Nyamagond, Ankit A. (International Journal of Research in Orthopaedics, 2022)
Trimalleolar fracture are complex and challenging to treat. We conducted a study on 15 patients with trimalleolar fracture. Fractures were classified based on Lauge Hansen classification. They were treated with open reduction and internal fixation (ORIF) with plate and screws for posterior malleolus and lateral malleolus, tension band wire (TBW)/cannulated cancellous (CC) screw for medial malleolus functional and radiological outcomes were assessed by Olerud and Molender score and Kristenson’s criteria respectively. Functional outcome was satisfactory in 93% of cases and radiological outcome in 86%. Early treatment without delay, anatomical reduction of fracture with stable fixation of every fracture component, stringent post operative mobilization should help to improve outcome in operated trimalleolar fracture patients.